The influence of population and unemployment on poverty in West Sumatra - Hafiz, M; Kurniadi, Anggi Putri (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2023)
The goals of this research are to determine how unemployment affects poverty, how population affects poverty, and how both factors together affect the poverty rate in 19 West Sumatra Province districts and cities. The study's methodology in West Sumatra Province employed a quantitative strategy with secondary data. employing a quantitative strategy with panel data regression and E-Views 12 software, utilizing secondary data obtained via BPS. The population has a considerable positive effect on the poverty rate, according to the study's results. Where this effect is seen, H0 is rejected and Ha1 is accepted, with a probability value of 0.000 t-table (5.25>1.98). and H0 is rejected and Ha2 is accepted. The unemployment rate has a negative and negligible impact on the poverty rate, where the probability value is 0.2815>0.05 with the value of t-count < t-table (-1.08 < 1.98). because the population and unemployment variables both significantly affect the poverty rate. In this case, H0 is rejected and Ha3 is accepted when the probability value is 0.000007 from the F-table (13.58>3.10).